(untitled) (Modern education and development, 2024)
Translation includes correcting grammatical discrepancies across languages in addition to translating words from one language to another. Variations in sentence structure, verb forms, tenses, articles, and word order give rise to these difficulties. This article examines frequent grammatical challenges that translators encounter, including tense usage, syntactic mismatches, and discrepancies in grammatical categories, and offers solutions.